Carbon risk and equity prices - Arthur Enders; Thomas Lontzek; Karl Schmedders; Marco Thalhammer (Financial Review, 2024)
Abstract We study the effects of carbon transition risk on equity prices in the United States and Europe using disclosed carbon intensity data and find a negative effect on the cross section~of returns and a negative carbon premium for the period 2009–2019. Examining fund flows, we find that institutional investors had an aversion to carbon-intensive stocks, which could help explain the outperformance of green stocks. We find that after the Paris Agreement this negative carbon premium disappears, and expect a positive premium in the future. We apply an asset-pricing approach to quantify the carbon risk exposure of any given~asset.
Keywords: 330; carbon emissions; carbon risk; climate change; equity returns; factor model; institutional investors